Pengaruh Bauran Pemasaran Terhadap Keputusan Mahasiswa Memilih Fakultas Ekonomi dan Bisnis Universitas Internasional Semen Indonesia di Gresik - Joko Pristiwanto; Nonni Yap; Djunaedi Djunaedi (Economic Reviews Journal, 2026)
This study analyzes the influence of the marketing mix on students’ decisions to choose the Faculty of Economics and Business at Semen Indonesia International University in Gresik. The marketing mix is focused on four main variables: product, price, place, and promotion. The study applies a quantitative approach by distributing questionnaires to students as respondents. Data are analyzed using descriptive statistics, validity and reliability tests, classical assumption testing, multiple linear regression, coefficient of determination, F-test, and t-test. The findings show that product, price, place, and promotion simultaneously have a significant influence on students’ choice decisions. Partially, product has a positive and significant effect, price has a significant effect with a negative direction, place has a positive and significant effect, while promotion does not have a significant effect. The Adjusted R Square value of 0.309 indicates that 30.9% of students’ choice decisions can be explained by the four marketing mix variables, while the remaining 69.1% is influenced by variables outside the model. These findings suggest that academic programs, cost suitability, campus accessibility, and promotional communication should be managed in an integrated manner to strengthen students’ confidence in choosing FEB UISI.